Nurses as 'guests'– a study of a concept in light of Jacques Derrida's philosophy of hospitality. (11th March 2013) - Öresland, Stina; Lutzén, Kim; Norberg, Astrid; Rasmussen, Birgit H.; Määttä, Sylvia
Abstract As revealed in previous empirical research, nurses describe their position in home‐based nursing care (HBNC) as that of 'guests' in the patient's home. Such a description is problematic as 'guests' might not be considered to belong to the realm of professionalism. As Jacques Derrida's work on hospitality has received wide publicity, sparking theoretical and philosophical discussion about host and guest, the aim of this study was to explore how the concept 'guests' can be understood in the light of Derrida's philosophy of hospitality. The study revealed that (a) guest must be considered a binary concept; and (b) hospitality should be regarded as an exchange of giving and receiving between a host and a guest. The present study demonstrated that it is important to reflect on the meaning of the concepts used by nurses in HBNC. Further theoretical and empirical exploration of the concept 'hospitality' would be fruitful, i.e. what is patients' understanding of 'hospitality' and 'hostility' related to nurses' descriptions of themselves as 'guests' in the patient's home.